Travelling in Romantic Bildungsroman Narratives - Nivala, Asko (Edinburgh University Press, 2025)
The early nineteenth-century bildungsroman is often understood as a coming-of-age story of the protagonist, which implies that temporality is more constitutive for its composition than spatiality. In contrast, my paper focuses on the motif of travelling in German and British bildungsroman narratives. Opposed to the previous allegorical understanding of the Romantic bildungsroman, I suggest that the methods of the spatial humanities open up a new perspective on bildungsroman narratives by showing how their travel itineraries were used in the construction of Europe before and after the Napoleonic Wars. The itineraries annotated from the corpus suggest that the classic Grand Tour to Italy remain important, especially in German Romanticism, whereas northern regions are also popular in British texts. A few narratives emphasise the region of Greece in defining the European frontier in relation to the Ottoman Empire, while Russia and Poland are not popular settings for bildungsroman narratives.